Perceived price, eTrust, eSatisfaction, and online repurchase intention: A study of young online consumer behavior - Khalikussabir , Khalikussabir; Waris, Abdul; Wahono, Budi (University of Islam Malang, 2022)
The online marketplace industry in Indonesia is growing rapidly, becoming an important contributor to Indonesia's economy. However, the massive discount price strategy and the dearth of face-to-face interaction in the online marketplace make it harder for any online retailer to build a stronger relationship with their consumers to retain them. Our study offers several contributions and new insights to the marketing literature as few studies have addressed this issue by analyzing it with perceived electronic trust, satisfaction, and repurchase intention into a single framework. This study aims to describe and extend previous studies on the effect of perceived price and trust on repurchase intention by specifically including satisfaction in the middle of associated constructs. This study uses purposive sampling as a sampling technique and a five-point Likert scale survey as a data collection method. A total of 387 valid data were collected and then analyzed by PLS-SEM to test the proposed model. The results of this study strengthen the previous claims that there is a positive partial effect between perceived price, trust, and satisfaction on repurchase intention in the online marketplace. Also, the level of customer satisfaction proved to be a significant construct in forming the association between perceived price, trust, and repurchase intention in the study.